Evaluasi Knee Ankle Foot Ortosis Dengan Parameter Spatiotemporal Dan Keseimbangan Pada Pengguna dengan Polio - Fika Trifani; Raden Achmad Candra Putra; Tri Riana Lestari (Quality : Jurnal Kesehatan, 2018)
The knee-ankle-foot orthosis (KAFO) tool is commonly described for patients with a history of poliomyelitis and serves to improve gait and prevent degeneration of the knee joint. However, at present the effect of using knee ankle foot orthosis in monoplegia polio patients when walking has never been evaluated. The purpose of this study was to analyze biomechanical adaptation especially in spatiotemporal parameters and stability when the subjects walked with and without KAFO aids. Methods: Fifteen monoplegia subjects with poliomyelitis were tested with two gait analyzes (i.e. with and without KAFO aids). Spatiotemporal parameters were tested using the 10 Meter Walk Test (10MWT) instrument, while stability when running was tested with the Timed up and Go (TUG) test instrument. Data from the spatiotemporal parameters obtained were analyzed using paired T tests, and the McNemar test was used to analyze the stability variables while walking. Both analyzes will analyze differences in parameters tested when subjects are in line with and without KAFO tools. Significant level used is p <0.05. Results: The results showed that there were significant differences in spatiotemporal parameters and stability when subjects walked with and without KAFO aids. This tool increases spatiotemporal parameters and stability when the subject runs using KAFO compared to when they did not use orthosis at all. When the stance phase in the leg is paralysis, hyperextension in the knee and excessive flexion of the knee is reduced, while flexion in the hip joint increases. Walking stability increased in 60% of subjects when they used KAFO when walking. This study found that gait compensation was also reduced when subjects walked using KAFO, and through direct feedback the subject stated that walking using KAFO made them not easily tired and could go further.